MACHINE CONDITION PROGNOSTICS: THE STATE OF THE ART - Stenly Tangkuman (Jurnal Tekno Mesin, 2018)
Prognostics is an inherent component of condition-based maintenance. It can assess the current healthof a part and predict into the future the health of a part for a fixed time horizon or predict the time tofailure. Since this topic has gained popularity in machine learning, however, researchers who applied inmachine prognostics (or prognosis) are relatively rare.With the aim of synthesizing and providing theinformation of these researches for researcher’s community, this paper attempts to summarize and classifythe recent published techniques in prognostics of rotating machinery. It reviews the papers upon the early2012. Furthermore, it also discusses the opportunities as well as the challenges for conducting advanceresearch in the field of machine prognostics.Keywords: Machine Fault, Condition Prognostics